Pendampingan Pengembangan Sumber Daya Manusia dalam Organisasi Remaja Masjid - Fitri, Abd. Basit Misbachul (Janaka, Jurnal Pengabdian Masyarakat, 2019)
The purpose of this study is to provide an in depth look at the experience of human resources development in the youth organization of Masjid Al Mutaqin. This is a qualitative study using the ABCD (asset based community Development) approach conducted in the village of Sawahan Lengkong Nganjuk. Data collection is done in a mosque in the local area by conducting deep interviews to informant, observations, documentation studies and recordings. The results of the analysis and research data to mention that the youth mosques in running their organization need to get assistance as the actual management concept, because during this time work and performance are still running as is and the reason is not based on organizational management theory.